2018
DOI: 10.3389/fphar.2018.00416
|View full text |Cite
|
Sign up to set email alerts
|

Brain Lipopolysaccharide Preconditioning-Induced Gene Reprogramming Mediates a Tolerance State in Electroconvulsive Shock Model of Epilepsy

Abstract: There is increasing evidence pointing toward the role of inflammatory processes in epileptic seizures, and reciprocally, prolonged seizures induce more inflammation in the brain. In this regard, effective strategies to control epilepsy resulting from neuroinflammation could be targeted. Based on the available data, preconditioning (PC) with low dose lipopolysaccharide (LPS) through the regulation of the TLR4 signaling pathway provides neuroprotection against subsequent challenge with injury in the brain. To te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Herein, we observed an upregulated mRNA expression of TLR4 and NF-κB in the second hit PTZ group. Our findings are in corroboration with earlier findings from rodents and clinical experimentation where TLR4 (Fu et al, 2017;Amini et al, 2018;Shi et al, 2018) and NF-κB level (Choo et al, 2018) has been reported to be upregulated in epileptic condition. We hypothesize an activation of the HMGB1-TLR4-NF-κB signaling pathway as evident by an upregulated mRNA expression level of HMGB1, TLR4, and NF-κB in second hit PTZ seizure model.…”
Section: Second Hit Ptz Induced Inflammatory Response Is Alleviated Bsupporting
confidence: 93%
See 1 more Smart Citation
“…Herein, we observed an upregulated mRNA expression of TLR4 and NF-κB in the second hit PTZ group. Our findings are in corroboration with earlier findings from rodents and clinical experimentation where TLR4 (Fu et al, 2017;Amini et al, 2018;Shi et al, 2018) and NF-κB level (Choo et al, 2018) has been reported to be upregulated in epileptic condition. We hypothesize an activation of the HMGB1-TLR4-NF-κB signaling pathway as evident by an upregulated mRNA expression level of HMGB1, TLR4, and NF-κB in second hit PTZ seizure model.…”
Section: Second Hit Ptz Induced Inflammatory Response Is Alleviated Bsupporting
confidence: 93%
“…Neuroinflammation and changes in the levels of related pro-inflammatory cytokines has been acknowledged to cause long-term alterations in the brain ( Amini et al, 2018 ). Plethora of pre-clinical and clinical studies has reported the presence and upregulation of inflammatory mediators (the brain, cerebrospinal fluid, and blood) in epileptic conditions ( Vezzani and Granata, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Four of the selected studies reported a general activation of inflammatory molecules and pathways together with neurogenesis in response to acute ECS up to 4 h after treatment. In a study using three ECS courses in a day to model epilepsy, the protein and mRNA expression of nuclear factor-kappa B (NF-κB) was increased and cell viability was decreased in rat hippocampus 1 h after the last treatment ( Amini et al, 2018 ). However, this was prevented in the hippocampus when a single or chronic dose of lipopolysaccharide (LPS) was injected intracerebroventricularly prior to ECS.…”
Section: Resultsmentioning
confidence: 99%
“…LPS also increased protein and mRNA levels of toll-like receptor 4 (TLR4), Src homology 2-containing inositol phosphatase-1 (SHIP1), toll interacting protein (TOLLIP), and interferon regulatory factor 3 (IRF3) after ECS, compared with vehicle group, and additionally increased the transcription of interferon-beta (IFN-β) and decreased that of TNF-α. They were also one of the few studies to assess behavioural outcomes, and noticed that LPS reduced the number of tonic–clonic seizures developed in response to ECS treatment ( Amini et al, 2018 ). Although TLR4 inactivation has previously been proposed as a target to reduce seizures ( Maroso et al, 2010 ), a recent study showed that stimulating the toll-like receptor 3 (TLR3), typically also considered pro-inflammatory and ictogenic, could actually prevent the emergence of seizures via IRF3/IFN-β rather than NF-κB signalling ( Kostoula et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Administration of a low dose of LPS (typically in the 0.05-1.0 mg/kg range) (Hickey et al, 2011) is one of the bestcharacterized approaches to yield neuroprotection via preconditioning. Acting via TLR4, LPS is thought to reprogram the intracellular response to a subsequent insult, resulting in broad neuroprotection via activation of antiinflammatory factors, alongside the downregulation of NF-kB (Hickey et al, 2011;Wang et al, 2015;Amini et al, 2018). One study compared young rats exposed to systemic low dose LPS at p6 and p30, followed by pilocarpine injection at 2 months of age, and reported that LPS at p30 only resulted in a reduction in acute seizures alongside ameliorated seizure-induced changes in microglial morphology (Kosonowska et al, 2015).…”
Section: Inflammatory Preconditioning-protection Against Epilepsy?mentioning
confidence: 99%